Negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery

By adjusting the particle size distribution and processing technology of graphite negative electrode materials, the problems of insufficient energy density, rate performance and cycle performance of graphite negative electrode materials in the existing technology are solved, and the consideration of high energy density, rate performance and high cycle performance are achieved, and the improvement of high energy density, rate performance and high cycle performance are achieved. The overall performance of lithium-ion batteries.

CN119324225AActive Publication Date: 2025-01-17BTR NEW MATERIAL GRP CO LTD +1

Patent Information

Application Number
CN202411850898.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-17
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing graphite anode materials have shortcomings in energy density, rate performance and cycle performance, and it is difficult to take into account high energy density, rate performance and high cycle performance.

Method used

A negative electrode material was prepared with a particle size distribution of 3.5 µm to 6.0 µm, D50 7.5 µm to 11.0 µm, D90 16.0 µm to 23.5 µm, oil absorption value of 28 mL/100g to 40 mL/100g, and The compaction density at 5T pressure is 1.70 g/cm3 to 1.85 g/cm3, which is formed by gradient heating and graphitization, ensuring the high energy density and good electrochemical properties of the material.

Benefits of technology

The high energy density, high rate performance and high cycle performance of the negative electrode material are achieved, and the overall performance of lithium-ion batteries is improved, especially in terms of high rate discharge and cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324225A_ABST
    Figure CN119324225A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material and a preparation method thereof, a negative electrode plate and a lithium ion battery, the negative electrode material comprises graphite, in the cumulative volume particle size distribution of the negative electrode material, the particle size D10 is 3.5 m to 6.0 m, the particle size D50 is 7.5 m to 11.0 m, and the particle size D90 is 16.0 m to 23.5 m; the oil absorption value dbq of the negative electrode material is 28 mL / 100 g to 40 mL / 100 g; the cocaine k of the negative electrode material is greater than or equal to 0.0386 and less than or equal to 0.176, # imgabs0 # and P.D (5T) are compaction densities of the negative electrode material under the pressure of 5T, and the unit is g / cm < 3 >. Based on the negative electrode material provided by the invention, the problems of poor energy density, rate capability and cycle performance of the graphite negative electrode material in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode material and a preparation method thereof, a negative electrode sheet and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, long service life and environmental friendliness. With the development of the market, lithium-ion batteries are not only widely used in mobile devices such as smartphones and portable computers, but also in large equipment such as electric vehicles and power tools.

[0003] As the key material of lithium-ion batteries, the performance parameters of negative electrode materials directly determine the performance indicators of lithium-ion batteries. Graphite negative electrode materials are widely used due to their good conductivity and charge and discharge stability, and have become the first choice for commercial negative electrode materials. Graphite negative electrode materials are divided into natural graphite negative electrode materials and artificial graphite negative electrode materials. Due to the advantages of artificial graphite such as easy graphitization, high conductivity, relatively low price and low ash content, artificial graphite negative electrode materials have become the mainstream products in the negative electrode material market in recent years. At present, artificial graphite negative electrode materials on the market are mainly used in power and energy storage. At present, artificial graphite negative electrode materials are mainly divided into two categories. One category has excellent cycle performance, but low gram capacity, compaction density and energy density. The other category has high gram capacity and compaction density, but there are difficulties in material processing. Moreover, when used as negative electrode materials for lithium-ion batteries, the battery cycle performance is poor, and the kinetic properties such as rate performance are poor. It is difficult to achieve high energy density, high rate performance and high cycle performance at the same time. With the continuous development of the lithium-ion battery industry, the requirements for graphite negative electrode materials are becoming higher and higher. It is of great significance to obtain graphite negative electrode materials that have high energy density, high rate performance and cycle performance. Summary of the invention

[0004] The main purpose of the present invention is to provide a negative electrode material and a preparation method thereof, a negative electrode sheet and a lithium ion battery, so as to solve the problems of poor energy density, rate performance and cycle performance of graphite negative electrode materials in the prior art.

[0005] To achieve the above object, according to one aspect of the present invention, a negative electrode material is provided, the negative electrode material comprises graphite, in the cumulative volume particle size distribution of the negative electrode material, the particle size D10 is 3.5 µm to 6.0 µm, the particle size D50 is 7.5 µm to 11.0 µm, and the particle size D90 is 16.0 µm to 23.5 µm; the oil absorption value dbq of the negative electrode material is 28 mL / 100 g to 40 mL / 100 g; the cocaine factor k of the negative electrode material is greater than or equal to 0.0386 and less than or equal to 0.176, wherein, PD (5T) is the compaction density of the negative electrode material at 5T pressure, in g / cm 3.

[0006] Furthermore, the compaction density of the negative electrode material at 5T pressure is 1.70 g / cm 3 Up to 1.85 g / cm 3 .

[0007] Further, the particle size Dn10 of the negative electrode material is 0.9 μm to 1.4 μm, the particle size Dn50 is 1.7 μm to 2.6 μm, and the particle size Dn90 is 5.0 μm to 7.0 μm.

[0008] Furthermore, in the cumulative volume particle size distribution of the negative electrode material, the volume proportion of the negative electrode material with a particle size in the range of 1 μm to 3 μm is 5.5% to 6.5%.

[0009] Furthermore, the graphite has a degree of graphitization of 89% to 92.5%.

[0010] Furthermore, the interlayer spacing between adjacent graphene sheets in graphite is 3.3600 Å to 3.3630 Å.

[0011] Furthermore, in terms of weight percentage, the Al content in the negative electrode material is not greater than 10 ppm.

[0012] Furthermore, the water content in the negative electrode material is no more than 0.05% by weight.

[0013] Furthermore, the repose angle of the negative electrode material is 50° to 65°.

[0014] Furthermore, the specific surface area of ​​the negative electrode material is 1.0 m 2 / g to 1.9 m 2 / g.

[0015] Further, the graphite includes artificial graphite and / or natural graphite.

[0016] Furthermore, the graphite includes at least one of petroleum coke-based graphite, asphalt coke-based graphite, and needle coke-based graphite.

[0017] Furthermore, the tap density of the negative electrode material after 1000 vibrations is 0.95 g / cm 3 Up to 1.3 g / cm 3 .

[0018] Furthermore, the first discharge capacity of the negative electrode material is 338 mAh / g to 343 mAh / g.

[0019] Furthermore, the first discharge efficiency of the negative electrode material is above 93%.

[0020] According to another aspect of the present invention, there is provided a method for preparing a negative electrode material, comprising the following steps:

[0021] Step S1, crushing the coke raw material to obtain a crushed material; wherein the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 3.5 μm to 6.0 μm, the particle size D50 is 7.5 μm to 11.0 μm, and the particle size D90 is 16.0 μm to 23.5 μm;

[0022] Step S2, under an inert gas atmosphere, heating the crushed material to a first temperature for a first heat treatment, heating the crushed material after the first heat treatment to a second temperature for a second heat treatment, heating the crushed material after the second heat treatment to a third temperature for a pre-carbonization treatment, the pre-carbonization treatment time is 8h to 15h; the first heat treatment temperature is 300°C to 500°C, the second heat treatment temperature is greater than or equal to 400°C and less than 800°C, the pre-carbonization treatment temperature is greater than or equal to 800°C and less than 1500°C; the second heat treatment temperature is greater than the first heat treatment temperature, and the pre-carbonization treatment temperature is greater than the second heat treatment temperature; the ratio of the first heat treatment time, the second heat treatment time and the pre-carbonization treatment time is (1-3): (2-4): (4-6);

[0023] Step S3, graphitizing the crushed material after the pre-carbonization treatment.

[0024] Furthermore, in step S1, the coke raw material includes at least one of petroleum coke, asphalt coke and needle coke.

[0025] Furthermore, in step S1, the coke raw material is crushed by jaw crusher and then crushed and shaped to obtain crushed material.

[0026] Furthermore, step S2 also includes, in the process of heating to the first temperature, heating to the second temperature and heating to the third temperature, respectively turning the crushed material over, and turning over for 10 min to 30 min every time the temperature rises by 100° C. to 300° C.

[0027] Furthermore, in step S2, the oxygen content in the inert atmosphere is no more than 5% by volume.

[0028] Furthermore, in step S3, the temperature of the graphitization treatment is greater than or equal to 2500°C and less than or equal to 3000°C.

[0029] Furthermore, in step S3, the holding time of the graphitization treatment is greater than or equal to 8 days and less than or equal to 10 days.

[0030] Furthermore, in step S2, the equipment for pre-carbonization treatment is a carbonization drum kiln.

[0031] Furthermore, in step S3, the furnace type for graphitization treatment is selected from any one of an inner series furnace, a box furnace, and an Acheson furnace.

[0032] According to another aspect of the present invention, a negative electrode sheet is provided, comprising a negative electrode current collector and a negative electrode active material layer bonded to the negative electrode current collector, wherein the negative electrode active material layer comprises the above negative electrode material or a negative electrode material prepared according to the above negative electrode material preparation method.

[0033] According to another aspect of the present invention, there is provided a lithium ion battery, comprising a negative electrode, wherein the electrode sheet used for the negative electrode is the negative electrode sheet as described above.

[0034] By applying the technical solution of the present invention, the particle size D10 of the negative electrode material is 3.5 µm to 6.0 µm, the particle size D50 is 7.5 µm to 11.0 µm, the particle size D90 is 16.0 µm to 23.5 µm, the oil absorption value dbq is 28 mL / 100 g to 40 mL / 100 g, and the coking factor, that is, the relationship between the particle size distribution, the compacted density PD (5T) and the oil absorption value dbq is in the range of 0.0386 to 0.176, and the negative electrode material has high energy density, high rate performance and high cycle performance; when D10, D50 and D90 are less than the above range, it is beneficial for lithium ions and electrolyte to enter the graphite, thereby obtaining a higher rate performance, but it is easy to cause irreversible embedding of lithium ions into the graphite, thereby deteriorating the cycle performance of the negative electrode material; when D10, D50 and D90 are greater than the above range, it is beneficial to improve the cycle performance of the negative electrode material and deteriorate the rate performance of the negative electrode material; when the particle size of the negative electrode material is in the above range, When dbq is within the above range, it is beneficial to obtain a graphite negative electrode with high cycle performance and high rate performance, and the large particles with larger particle size and the small particles with smaller particle size of the negative electrode material can cooperate with each other, and the small particles fill the pores between the large particles, which is beneficial to improve the energy density of the negative electrode material; dbq is within the above range, which is beneficial to the entry of lithium ions and electrolyte into graphite and is beneficial to reducing the irreversible embedding of lithium ions, thereby obtaining higher cycle performance and rate performance; when the relationship between compaction density, particle size distribution, and oil absorption value satisfies the above range, the negative electrode material has a higher compaction density and energy density, and is beneficial to the entry of lithium ions and electrolyte into graphite and the reversible embedding of lithium ions, thereby obtaining a negative electrode material with high energy density, high rate performance and high cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0036] Figure 1 A schematic structural diagram of an electrode assembly is shown;

[0037] Figure 2 The SEM image of the negative electrode material prepared according to Example 1 of the present invention is shown.

[0038] The above drawings include the following reference numerals:

[0039] 1. Positive electrode sheet; 11. Positive electrode current collector; 12. Positive electrode active layer;

[0040] 2. Negative electrode sheet; 21. Negative electrode current collector; 22. Negative electrode active material layer;

[0041] 3. Isolation film. DETAILED DESCRIPTION

[0042] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0043] An embodiment of the present application provides a secondary battery, such as a lithium-ion battery, a sodium-ion battery, etc., including a housing, an electrode assembly, and an electrolyte, wherein the electrode assembly and the electrolyte are both located in the housing.

[0044] The outer shell can be a packaging bag obtained by packaging with a packaging film (such as an aluminum-plastic film), such as a soft-pack battery. In some embodiments, the secondary battery can also be a steel shell battery, an aluminum shell battery, etc.

[0045] like Figure 1 As shown, the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is disposed between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2. In some embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence and then winding them.

[0046] The positive electrode sheet 1 includes a positive electrode current collector 11 and a positive electrode active layer 12 provided on at least one surface of the positive electrode current collector 11. The positive electrode current collector 11 can be made of aluminum foil or nickel foil, etc., or it can be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and the polymer substrate. The positive electrode active layer 12 contains a positive electrode active material, and the positive electrode active material includes a compound that can reversibly embed and deintercalate metal ions. In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide, a sodium transition metal composite oxide, etc. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5O4) or at least one of lithium iron phosphate (LiFePO4).

[0047] The negative electrode sheet 2 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on at least one surface of the negative electrode current collector. The negative electrode current collector 21 can use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or can be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer includes a negative electrode material.

[0048] As described in the background art, the graphite negative electrode materials in the prior art have the problem that high energy density, high rate performance and high cycle performance are difficult to take into account. In addition, in the development and application of graphite negative electrode materials, the control of particle size is one of the key factors in optimizing material performance. In the existing preparation of negative electrode materials, graphite particles with larger particle sizes are often used in order to obtain better electrochemical properties, mechanical strength and processing properties, and the utilization efficiency of graphite micropowder is not high. However, this ignores the potential advantages of small-particle graphite in improving battery energy density, improving lithium ion transmission rate, etc. In order to make full use of small-particle graphite and simultaneously obtain a negative electrode material with high energy density, high rate performance and high cycle performance, the present invention provides a negative electrode material, the negative electrode material includes graphite, in the cumulative volume particle size distribution of the negative electrode material, the particle size D10 is 3.5 µm to 6.0 µm, the particle size D50 is 7.5 µm to 11.0 µm, and the particle size D90 is 16.0 µm to 23.5 µm; the oil absorption value dbq of the negative electrode material is 28 mL / 100 g to 40 mL / 100 g; the coca factor k of the negative electrode material is greater than or equal to 0.0386 and less than or equal to 0.176, wherein, PD (5T) is the compaction density of the negative electrode material at 5T pressure, in g / cm 3 .

[0049] In order to obtain a high-performance graphite negative electrode material, the present invention provides a negative electrode material, wherein the particle size D10 of the negative electrode material is 3.5 μm to 6.0 μm, the particle size D50 is 7.5 μm to 11.0 μm, and the particle size D90 is 16.0 μm to 23.5 µm, the oil absorption value dbq is 28mL / 100g to 40mL / 100g, and the coca factor, that is, the relationship between the particle size distribution, the compacted density PD (5T) and the oil absorption value dbq is in the range of 0.0386 to 0.176, the negative electrode material has high energy density, high rate performance and high cycle performance; when D10, D50 and D90 are less than the above range, it is beneficial for lithium ions and electrolyte to enter the graphite, thereby obtaining a higher rate performance, but it is easy to cause irreversible embedding of lithium ions into the graphite, thereby deteriorating the cycle performance of the negative electrode material; when D10, D50 and D90 are greater than the above range, it is beneficial to improve the cycle performance of the negative electrode material and deteriorate the rate performance of the negative electrode material; when the particle size of the negative electrode material is in the above range, it is beneficial to improve the cycle performance of the negative electrode material and deteriorate the rate performance of the negative electrode material. When dbq is within the above range, it is beneficial to obtain a graphite negative electrode with high cycle performance and high rate performance, and the large particles with larger particle size and the small particles with smaller particle size of the negative electrode material can cooperate with each other, and the small particles fill the pores between the large particles, which is beneficial to improve the energy density of the negative electrode material; dbq is within the above range, which is beneficial to the entry of lithium ions and electrolyte into graphite and is beneficial to reducing the irreversible embedding of lithium ions, thereby obtaining higher cycle performance and rate performance; when the relationship between compaction density, particle size distribution, and oil absorption value satisfies the above range, the negative electrode material has a higher compaction density and energy density, and is beneficial to the entry of lithium ions and electrolyte into graphite and the reversible embedding of lithium ions, thereby obtaining a negative electrode material with high energy density, high rate performance and high cycle performance.

[0050] In the above embodiments, the particle size D10 of the negative electrode material is 3.5 µm to 6.0 µm, and can be 3.5 µm, 3.8 µm, 4.0 µm, 4.2 µm, 4.5 µm, 4.8 µm, 5 µm, 5.2 µm, 5.5 µm, 5.8 µm or 6.0 µm. Of course, it can also be other values ​​within the above range, which is not limited here.

[0051] In the above embodiments, the particle size D50 of the negative electrode material is 7.5 µm to 11.0 µm, and can be specifically 7.5 µm, 8 µm, 8.3 µm, 8.5 µm, 8.8 µm, 9 µm, 9.2 µm, 9.5 µm, 9.8 µm, 10 µm, 10.5 µm or 11.0 µm. Of course, it can also be other values ​​within the above range, which is not limited here.

[0052] In the above embodiment, the particle size D90 of the negative electrode material is 16.0 µm to 23.5 µm, and can be specifically 16.0 µm, 16.5 µm, 17.0 µm, 17.5 µm, 18.0 µm, 18.5 µm, 19.0 µm, 19.5 µm, 20.0 µm, 20.5 µm, 21.0 µm, 21.5 µm, 22.0 µm, 22.5 µm, 23.0 µm, 23.5 µm. Of course, it can also be other values ​​within the above range, which is not limited here.

[0053] Among them, the particle size D10 represents the particle size corresponding to 10% of the cumulative volume percentage of the powder in the volume distribution of the negative electrode material, D50 represents the particle size corresponding to 50% of the cumulative volume percentage, and D90 represents the particle size corresponding to 90% of the cumulative volume percentage.

[0054] In some embodiments, the compaction density of the negative electrode material at 5T pressure is 1.70 g / cm 3 Up to 1.85 g / cm 3 The compacted density can be 1.70 g / cm 3 , 1.72 g / cm 3 , 1.74 g / cm 3 , 1.76g / cm 3 , 1.78 g / cm 3 , 1.80 g / cm 3 , 1.82 g / cm 3 , 1.84 g / cm 3 or 1.85 g / cm 3 Of course, it can also be other values ​​within the above range, which is not limited here. The compaction density of the negative electrode material significantly affects the energy density and conductivity of the lithium-ion battery. Under this compaction density, the lithium-ion battery has a higher energy density and charge and discharge efficiency, and also has higher cycle performance and rate performance.

[0055] In some embodiments, the particle size Dn10 of the negative electrode material is 0.9 μm to 1.4 μm, the particle size Dn50 is 1.7 μm to 2.6 μm, and the particle size Dn90 is 5.0 μm to 7.0 μm. The particle size Dn10 of the negative electrode material can be 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.0 μm, 1.4 μm, and of course it can also be other values ​​within the above range, which is not limited here. The particle size Dn50 can be 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, and the particle size Dn90 can be 5.0 μm, 5.5 μm, 5.8 μm, 6.0 μm, 6.2 μm, 6.5 μm, 6.8 μm, 7.0 μm, and of course it can also be other values ​​within the above range, which is not limited here. Among them, the particle size Dn10 represents the particle size corresponding to 10% of the cumulative number percentage of the powder in the negative electrode material quantity distribution, Dn50 represents the particle size corresponding to 50% of the cumulative number percentage, and Dn90 represents the particle size corresponding to 90% of the cumulative number percentage. The quantity distribution focuses on the counting ratio of particles within a specific size range. It reflects the absolute number of particles of each size in the sample. The volume distribution focuses on the total volume ratio of particles within a specific size range. It reflects the space ratio occupied by particles of each size in the sample. Unlike the quantity distribution, if the number of large-sized particles is small, but because of the large volume, they may also occupy a larger proportion of the total volume. Negative electrode materials with smaller particle sizes have larger initial capacity, but also larger irreversible capacity. As the particle size increases, the initial charge and discharge capacity decreases, and the irreversible capacity decreases. At the same time, the smaller the negative electrode material particles, the larger the specific surface area in contact with the electrolyte, the more charge is consumed by the SEI film formed during the initial charge and discharge process, and the greater the irreversible capacity loss. The negative electrode material with the above-mentioned particle size distribution can improve the initial capacity, initial efficiency and lithium ion cycle performance of the lithium-ion battery, and help increase the compaction density of the electrode sheet, thereby improving the volume energy density of the lithium-ion battery.

[0056] In some embodiments, in the cumulative volume particle size distribution of the negative electrode material, the volume proportion of the negative electrode material in the range of 1 μm to 3 μm is 5.5% to 6.5%, specifically 5.5%, 5.8%, 5.9%, 6.0%, 6.0%, 6.2%, 6.5%, and of course other values ​​within the above range, which are not limited here. Smaller particles can provide better rate performance because they have a larger surface area, which is conducive to the rapid transmission of lithium ions during the charge and discharge process. Under the above volume proportion, the negative electrode material is more conducive to fast charging to achieve a fully intercalated lithium state, thereby having better full discharge performance and can improve the cycle performance of lithium ions.

[0057] In some embodiments, the graphitization degree of graphite is 89% to 92.5%, and the interlayer spacing between adjacent graphite sheets in the graphite is 3.3600Å to 3.3630Å. The graphitization degree can be 89%, 89.5%, 90%, 90.5%, 99%, 90.5%, 91%, 91.5%, 92%, 92.5%, and of course, it can be other values ​​within the above range, which are not limited here. At the above graphitization degree, the graphite has a high degree of graphitization, and the negative electrode material has good conductivity, compatibility with the electrolyte, and high temperature performance. The above interlayer spacing range is conducive to the insertion and extraction of lithium ions, thereby facilitating the acquisition of a negative electrode material with higher cycle performance and rate performance.

[0058] In some embodiments, the Al content in the negative electrode material is not more than 10ppm by weight, and the Al content can be 0ppm, 1ppm, 2ppm, 3ppm, 4ppm, 5ppm, 6ppm, 7ppm, 8ppm, 9ppm, 10ppm, and of course other values ​​within the above range, which are not limited here. In the electrolyte system of lithium-ion batteries, CMC (carboxymethyl cellulose) is an important binder, which is crucial to the rheology of electrode slurry and the mechanical strength of pole pieces. Metallic Al ions can complex with CMC, causing CMC molecules to lose their bonding properties, thereby reducing the viscosity of the slurry and affecting the uniformity and stability of the electrode slurry. By limiting the Al content in the negative electrode material to an extremely low level (not more than 10ppm), the complexation of Al ions with CMC is effectively reduced, ensuring the high viscosity and uniformity of the slurry, thereby improving the processing performance of the electrode and the stability of the finished lithium-ion battery. In addition, low content of Al element is beneficial to reduce electrochemical side reactions inside lithium-ion batteries, especially the chemical reaction between Al ions and components in the electrolyte, thereby reducing the risk of capacity attenuation of lithium-ion batteries during storage.

[0059] In some embodiments, the water content in the negative electrode material is no more than 0.05% by weight, and the water content can be specifically 0, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, and of course, it can be other values ​​within the above range, which are not limited here. Controlling the water content of the negative electrode material below 0.05% is conducive to improving the stability of the negative electrode material during processing, and the lower water content reduces the energy consumption during the drying process, speeds up the production speed, and reduces the fluctuation of electrode performance caused by uneven water evaporation.

[0060] In some embodiments, the angle of repose of the negative electrode material is 50° to 65°, and the angle of repose can be 50°, 52°, 54°, 56°, 58°, 60°, 62°, 64° or 65°, and of course it can be other values ​​within the above range, which are not limited here. When the angle of repose is within the above range, the particle size distribution of the negative electrode material is more uniform, the shape is more regular, the surface is smoother, and it has a higher compaction density and fluidity, which is conducive to obtaining a higher energy density, and is conducive to the coating of the negative electrode material to form a uniform film layer, thereby improving its cycle performance.

[0061] In some embodiments, the specific surface area of ​​the negative electrode material is 1.0 m 2 / g to 1.9 m 2 / g, and the specific surface area can be specifically 1.0 m 2 / g, 1.1 m 2 / g, 1.2 m 2 / g, 1.3 m 2 / g, 1.4 m 2 / g, 1.5 m 2 / g, 1.6 m 2 / g, 1.7 m 2 / g, 1.8m 2 / g, 1.9 m 2 / g, of course, it can also be other values ​​within the above range, which is not limited here. Under the above specific surface area, there are many channels for lithium ion migration, the path is short, the rate performance is good, and the contact area with the electrolyte is large, which is conducive to the formation of SEI film and the improvement of the initial efficiency.

[0062] In some embodiments, the graphite includes at least one of petroleum coke-based graphite, asphalt coke-based graphite, and needle coke-based graphite. The above types of graphite have low impurity content, which is beneficial to improving the electrochemical performance of the negative electrode material.

[0063] In some embodiments, the graphite includes artificial graphite and / or natural graphite.

[0064] In some embodiments, the tap density of the negative electrode material after 1000 vibrations is 0.95 g / cm 3 Up to 1.3 g / cm 3 The tap density can be 0.95 g / cm 3 , 1 g / cm 3 , 1.05 g / cm 3 , 1.10 g / cm 3 , 1.15 g / cm 3 , 1.20g / cm 3 , 1.25 g / cm 3 , 1.3 g / cm 3Of course, it can also be other values ​​within the above range, which is not limited here. At the above tap density, it has better electrical conductivity, thermal conductivity and corrosion resistance, and is beneficial to the slurry processing performance and slurry consistency.

[0065] In some embodiments, the first discharge capacity of the negative electrode material is 338mAh / g to 343mAh / g. The first discharge capacity can be 338mAh / g, 339mAh / g, 340mAh / g, 341mAh / g, 342mAh / g, and 343mAh / g. Of course, it can also be other values ​​within the above range, which is not limited here. At the above first discharge capacity, the negative electrode material has a lower electrochemical expansion, which is beneficial to the cycle life and kinetic performance of the lithium-ion battery.

[0066] In some embodiments, the first discharge efficiency of the negative electrode material is above 93%, and the first discharge efficiency can specifically be 93%, 93.2%, 93.4%, 93.6%, 93.8%, 94%, 94.2%, 94.4%, 94.6%, 94.8%, 95%, and of course other values ​​within the above range, which are not limited here. At the above first discharge efficiency, it is beneficial to improve the high and low temperature storage performance and kinetic performance of lithium-ion batteries.

[0067] According to another aspect of the present invention, there is provided a method for preparing a negative electrode material, comprising the following steps:

[0068] Step S1, crushing the coke raw material to obtain a crushed material; wherein the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 3.5 μm to 6.0 μm, the particle size D50 is 7.5 μm to 11.0 μm, and the particle size D90 is 16.0 μm to 23.5 μm;

[0069] Step S2, under an inert gas atmosphere, heating the crushed material to a first temperature for a first heat treatment, heating the crushed material after the first heat treatment to a second temperature for a second heat treatment, heating the crushed material after the second heat treatment to a third temperature for a pre-carbonization treatment, the pre-carbonization treatment time is 8h to 15h; the first heat treatment temperature is 300°C to 500°C, the second heat treatment temperature is greater than or equal to 400°C and less than 800°C, the pre-carbonization treatment temperature is greater than or equal to 800°C and less than 1500°C; the second heat treatment temperature is greater than the first heat treatment temperature, and the pre-carbonization treatment temperature is greater than the second heat treatment temperature; the ratio of the first heat treatment time, the second heat treatment time and the pre-carbonization treatment time is (1-3): (2-4): (4-6);

[0070] Step S3, graphitizing the crushed material after the pre-carbonization treatment.

[0071] Precarbonization is an important process link in the production of artificial graphite, but in the production process, the problem of precarbonization agglomeration often occurs. The main reasons include: (1) the particle size of the raw material powder is uneven; (2) the powder contains impurities; (3) the temperature is uneven during the precarbonization process, causing local overheating. The present invention provides a method for preparing a negative electrode material, the coke raw material is crushed to obtain a crushed material with a specific particle size distribution, and then a gradient heating treatment (first heat treatment and second heat treatment) is performed to fully volatilize and remove impurities with different boiling points in turn to reduce the adhesion of the raw materials in the subsequent precarbonization and graphitization treatments, and also to ensure that the heat is uniform during the precarbonization process. By reasonably allocating the heating time in each stage, the material can be effectively prevented from agglomerating. Finally, graphite is formed through graphitization treatment and there is basically no agglomeration between the graphites. The prepared negative electrode material satisfies the particle size D10 of 3.5 µm to 6.0 µm, the particle size D50 of 7.5 µm to 11.0 µm, and the particle size D90 of 16.0 µm to 23.5 μm, which is conducive to obtaining negative electrode materials with high cycle performance and high rate performance, and the filling and matching between the particles of different particle sizes is conducive to obtaining negative electrode materials with high energy density; in addition, the negative electrode materials prepared by the present invention have no agglomeration and aggregation, and have good dispersibility, which is conducive to the entry of lithium ions and electrolyte into graphite, thereby improving the rate performance of the negative electrode materials; furthermore, the first heat treatment helps the impurities in the material to fully volatilize to the surface of the coke raw material, and the subsequent second heat treatment continuously removes volatiles, pre-carbonization treatment and graphitization treatment to form a relatively smooth surface of the negative electrode material, reduce edges and roughness, and help reduce the consumption of electrolyte, improve the utilization efficiency of the electrolyte and improve the cycle performance of the negative electrode material, and the reduction of edges and corners Less is conducive to reducing the transmission resistance of lithium ions on the surface of the material, which helps to improve the capacity retention rate and overall performance of lithium-ion batteries under high-rate discharge. The second heat treatment can remove the volatiles on the surface of the coke raw material in one step, reduce the edges and roughness of the negative electrode material, and help reduce defects such as microcracks and pores on the surface of the negative electrode material after pre-carbonization and graphitization, thereby increasing the service life of the negative electrode material. In the entire process, the coke raw material is only crushed and refined in the initial stage, and no crushing and refinement treatment is performed subsequently. The surface of the negative electrode material is regular and has few defects, which improves the compaction density and energy density of the negative electrode material, thereby obtaining a negative electrode material with high energy density, high rate performance and high cycle performance.

[0072] In some embodiments, in step S1, the coke raw material includes at least one of petroleum coke, pitch coke, and needle coke. Preferably, when producing artificial negative electrode materials, petroleum coke with low sulfur content and high aromatic content is selected as the raw material to reduce the impurity content in subsequent processing and improve the electrochemical performance of the negative electrode material.

[0073] In some embodiments, in step S1, the coke raw material is crushed by a jaw crusher and then crushed and shaped to obtain a crushed material.

[0074] In the above embodiment, the jaw crushing is performed by a jaw crusher. The jaw crushing is performed by a jaw crusher, which has high output and low cost.

[0075] In the above embodiment, the crushing and shaping equipment includes a crushing equipment and a shaping equipment. The crushing equipment and the shaping equipment can adopt conventional equipment in the field. For example, the crushing equipment can adopt LCR1200, LCR1600, LHJ500 or LHJ750, which are not listed here one by one. The shaping equipment can adopt YQ600, LHZ15 or QH300-AF400, which are not listed here one by one.

[0076] In some embodiments, step S2 further includes, in the process of heating to the first temperature, heating to the second temperature, and heating to the third temperature, respectively turning the crushed material over, and turning over for 10 min to 30 min every time the temperature rises by 100° C. to 300° C.;

[0077] In some embodiments, in step S2, the oxygen content in the inert atmosphere is no more than 5% by volume, and the oxygen content can specifically be 0%, 1%, 2%, 3%, 3%, and 5%. At the above oxygen content, it is beneficial to reduce the oxidation of the crushed material, reduce the entry of impurities into the material, and improve the purity and quality of the graphite.

[0078] In some embodiments, in step S3, the temperature of the graphitization treatment is greater than or equal to 2500°C and less than or equal to 3000°C. The temperature of the graphitization treatment can specifically be 2500°C, 2550°C, 2600°C, 2650°C, 2700°C, 2750°C, 2800°C, 2850°C, 2900°C, 2950°C, 3000°C. Of course, it can also be other values ​​within the above range, which are not limited here. Within the above temperature range, the negative electrode material has a high degree of graphitization and high crystallinity, and the negative electrode material has better thermal stability and conductivity. The interlayer spacing of the graphite obtained within the temperature range is conducive to the embedding and de-embedding of lithium ions, thereby obtaining a negative electrode material with higher cycle performance and rate performance, and low energy consumption.

[0079] In order to obtain a negative electrode material with higher cycle performance and rate performance, in some embodiments, in step S3, the insulation time of the graphitization treatment is greater than or equal to 8 days and less than 10 days, specifically 8 days, 9 days, 10 days, and of course other values ​​within the above range, which are not limited here.

[0080] In some embodiments, in step S2, the pre-carbonization treatment equipment is a carbonization drum kiln, or other high-temperature heating equipment that can provide an inert gas atmosphere, which are not listed here. The carbonization drum kiln can be turned over, which is more conducive to preventing agglomeration during the carbonization process of the sample.

[0081] In some embodiments, in step S3, the furnace type for graphitization treatment is selected from any one of an inner series furnace, a box furnace, and an Acheson furnace.

[0082] According to another aspect of the present invention, a negative electrode sheet is provided, comprising a negative electrode current collector and a negative electrode active material layer bonded to the negative electrode current collector, wherein the negative electrode active material layer comprises the above negative electrode material or a negative electrode material prepared according to the above negative electrode material preparation method.

[0083] According to another aspect of the present invention, there is provided a lithium ion battery, comprising a negative electrode, wherein the electrode sheet used for the negative electrode is the negative electrode sheet as described above.

[0084] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0085] Example 1

[0086] A method for preparing a negative electrode material comprises the following steps:

[0087] Step 1, crushing the coke raw material by jaw crusher and then crushing and shaping it by crushing and shaping equipment to obtain a crushed material; wherein the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 4.1µm, D50 is 10.0µm, and D90 is 21.1µm; wherein the coke raw material is petroleum coke, wherein, by weight percentage, the volatile matter content in the coke raw material is 10%, the water content is 8%, the S content is 0.4%, and the iron content is 300ppm;

[0088] Step 2: In an inert gas atmosphere, the crushed material is heated to 400°C for a first heat treatment, the crushed material after the first heat treatment is heated to 600°C for a second heat treatment, and the crushed material after the second heat treatment is heated to 1200°C for a pre-carbonization treatment, and the pre-carbonization treatment time is 12 hours; wherein, the ratio of the first heat treatment time, the second heat treatment time and the pre-carbonization treatment time is 2:3:5, and the crushed material is turned over during the process of heating to 400°C, 600°C and 1200°C, and the turning is performed for 20 minutes every time the temperature rises by 200°C;

[0089] Step 3: graphitizing the pre-carbonized crushed material at 2600° C. for 10 days.

[0090] The SEM of the negative electrode material prepared in this example is as follows Figure 2 As shown in the figure, the prepared negative electrode material is granular, with no adhesion between particles, high dispersion and smooth and regular surface. The measured particle size D10 is 4.1 µm, the particle size D50 is 10.0 µm, the particle size D90 is 21.1 µm, and the specific surface area is 1.30 m 2 / g, tap density is 0.97 g / cm3 The compacted density at 5T pressure is 1.75 g / cm 3 , the oil absorption value is 36.6 mL / 100 g, the coke factor is 0.081, the first discharge capacity of the CR2016 button half-cell is 343.0 mAh / g, and the first discharge efficiency is 94.3%, as shown in Tables 1 and 2 for details.

[0091] Example 2

[0092] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 4.7 μm, D50 is 10.7 μm, and D90 is 21.8 μm.

[0093] Example 3

[0094] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 4.2 μm, D50 is 9.3 μm, and D90 is 17.8 μm.

[0095] Example 4

[0096] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 4.0 μm, D50 is 8.9 μm, and D90 is 16.1 μm.

[0097] Example 5

[0098] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 5.2 μm, D50 is 9.7 μm, and D90 is 19.8 μm.

[0099] Example 6

[0100] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 6.0 μm, D50 is 11.0 μm, and D90 is 16.1 μm.

[0101] Example 7

[0102] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 3.5 µm, D50 is 7.5 µm, and D90 is 23.4 µm.

[0103] Example 8

[0104] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 5.0 μm, D50 is 9.6 μm, and D90 is 19.4 μm, and the graphitization time in step three is 13 days.

[0105] Example 9

[0106] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 5.2 μm, D50 is 9.8 μm, D90 is 20.0 μm, and the graphitization temperature is 2300°C;

[0107] Example 10

[0108] The only difference from Example 1 is that the graphitization temperature is 2300°C.

[0109] Embodiment 11

[0110] The only difference from Example 1 is that the graphitization temperature is 3200°C.

[0111] Example 12

[0112] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 3.6 μm, D50 is 9.9 μm, and D90 is 18.2 μm.

[0113] Embodiment 13

[0114] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 5.9 μm, D50 is 10.4 μm, and D90 is 23.4 μm.

[0115] Embodiment 14

[0116] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 5.9 μm, D50 is 10.9 μm, and D90 is 22.7 μm.

[0117] Embodiment 15

[0118] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 3.5 μm, D50 is 7.6 μm, and D90 is 17.0 μm.

[0119] Comparative Example 1

[0120] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 6.0 μm, D50 is 10.3 μm, and D90 is 15.0 μm.

[0121] Comparative Example 2

[0122] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 3.6 μm, D50 is 7.6 μm, and D90 is 28 μm.

[0123] Comparative Example 3

[0124] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 6.8 μm, D50 is 9.8 μm, and D90 is 18.2 μm.

[0125] Comparative Example 4

[0126] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 5.8 μm, D50 is 11.7 μm, and D90 is 23.5 μm.

[0127] Comparative Example 5

[0128] The only difference from Example 1 is that the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 3.8 μm, D50 is 7.0 μm, and D90 is 16.3 μm.

[0129] Comparative Example 6

[0130] The only difference between it and Example 2 is that the first heat treatment is not performed in step 2. Step 2 is specifically as follows:

[0131] Under an inert gas atmosphere, the crushed material is heated to 600°C for a second heat treatment, and the crushed material after the second heat treatment is heated to 1200°C for a pre-carbonization treatment, and the pre-carbonization treatment time is 12 hours; wherein, the ratio of the second heat treatment time to the pre-carbonization treatment time is 3:5, and the crushed material is turned over during the process of heating to 600°C and heating to 1200°C, and is turned over for 20 minutes every time the temperature rises by 200°C.

[0132] Comparative Example 7

[0133] The only difference between it and Example 2 is that the second heat treatment is not performed in step 2. Step 2 is specifically as follows:

[0134] Under an inert gas atmosphere, the crushed material is heated to 400°C for a first heat treatment, and the crushed material after the first heat treatment is heated to 1200°C for a pre-carbonization treatment, and the pre-carbonization treatment time is 12 hours; wherein, the ratio of the first heat treatment time to the pre-carbonization treatment time is 2:5, and the crushed material is turned over during the process of heating to 400°C and heating to 1200°C, and is turned over for 20 minutes every time the temperature rises by 200°C.

[0135] Comparative Example 8

[0136] The only difference between it and Example 2 is that the first heat treatment and the second heat treatment are not performed in step 2. Step 2 is specifically as follows:

[0137] In an inert gas atmosphere, the crushed material was heated to 1200°C for pre-carbonization treatment, and the pre-carbonization treatment time was 12 hours. During the heating process to 1200°C, the crushed material was turned over, and the turning time was 20 minutes every time the temperature was increased by 200°C.

[0138] The performance tests were conducted on the negative electrode materials prepared in the examples and comparative examples, and the specific contents are as follows:

[0139] 1. Particle size test: The particle size was measured using Mastersizer 3000 laser diffraction technology. The measured D10, D50, D90, Dn10, Dn50, and Dn90 are shown in Table 1.

[0140] 2. Tap density test: Use a tap density meter (U.S. Quantachrome, DAT-6-220) to test the tap density of the material. The specific steps are as follows: Place the sample in a measuring cylinder and vibrate it 1000 times. Read the volume of the measuring cylinder after vibration and calculate the tap density. The tap density test results are shown in Table 1.

[0141] 3. The specific surface area of ​​the material was tested by nitrogen adsorption-desorption test (BET method). The test results are shown in Table 1.

[0142] 4. The compaction density of the sample at 5T was tested using a compaction density meter (Carver 4350). The test results are shown in Table 1.

[0143] 5. Graphitization degree and interlayer spacing test: The test was conducted using a Rigaku X-ray diffractometer. The test results are shown in Table 2.

[0144] 6. Al element content test: ICP spectrometer was used for testing. The test results are shown in Table 2.

[0145] 7. Water content test: Karl Fischer titrator was used for testing. The test results are shown in Table 2.

[0146] IX. Repose angle test: The test was conducted using the Hosokawa comprehensive tester. The test results are shown in Table 2.

[0147] 10. Oil absorption value test: Use an oil absorption value tester (ASAHI SOUKEN, Japan, S-500), take a powder sample and put it into the mixing chamber, then drip oil (DBP) into the sample at a constant rate, and stir it at the same time with a rotating wing at a speed of 630r / min. By detecting the viscosity change of torque, the oil absorption value (mL / 100g) of the sample is calculated. The oil absorption value data is shown in Table 2.

[0148] 11. Battery performance test:

[0149] Preparation of CR2016 button half-cell: The negative electrode materials prepared in the embodiment and the comparative example were mixed in a mass ratio of negative electrode material, conductive carbon black, CMC, and SBR of 95.3:1.5:1.4:1.8, and the negative electrode slurry was prepared with deionized water as solvent, and coated on copper foil with a coating surface density of 6.5±0.1 mg / cm 2 After vacuum drying at 90℃, the product was rolled to a compacted density of 1.50±0.02 g / cm 3 , and obtain the electrode; the dried negative electrode is used as the working electrode, metallic lithium is used as the counter electrode, the diaphragm is Celgard 2400, and the electrolyte is 1 mol·L -1 LiPF6 (wherein the solvent is EC (ethylene carbonate) / DMC (dimethyl carbonate) / EMC (ethyl methyl carbonate), and the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:1:1), CR2016 type button half-cell assembly is completed in a glove box filled with high-purity argon.

[0150] Preparation of full battery: The negative electrode materials prepared in each embodiment and comparative example were dissolved in deionized water according to the mass percentage of negative electrode active material, conductive agent, binder and dispersant of 95.2:1.5:2:1.3, and the solid content was controlled to be 50% (by weight percentage), and coated on an 8μm thick copper foil current collector, and vacuum dried to obtain a negative electrode plate; lithium iron phosphate, polyvinylidene fluoride and conductive agent carbon black were mixed with solvent NMP (N-methylpyrrolidone) in a mass ratio of 95:2:3, and then coated on a 16μm thick aluminum foil, and vacuum dried to obtain a positive electrode plate; the coated positive and negative electrode plates were subjected to sheet making, winding, drying, liquid injection, sealing, formation, volume separation and other processes to make a 554065 type soft-pack lithium-ion battery.

[0151] First discharge capacity and first discharge efficiency test: CR2016 button half-cell was tested on a blue battery tester at 25±2℃. The charge and discharge conditions were as follows: discharge: 0.1C to 0.005V; then 0.09C, 0.08C…0.02C to 0.001V; charge: 0.1C to 1.5V. The test results of the first discharge capacity and first discharge efficiency are shown in Table 2.

[0152] Rate performance test: The CR2016 button half-cell was tested on an Arbin battery tester at 25±2℃ to obtain the charge and discharge specific capacity and coulombic efficiency of 0.2C and 2C. Among them, the charge and discharge conditions are as follows: ①0.1C discharge to 0.01V, constant voltage for 5h; 0.1C charge to 1.5V; ②0.2C discharge to 0.01V, constant voltage 0.01C; 0.2C charge to 1.5V; ③0.2C discharge to 0.01V, constant voltage 0.01C; 2C charge to 1.5V, 0.2C charge to 1.5V; ④0.2C discharge to 0.01V, constant voltage 0.01C; 0.2C charge to 1.5V; ⑤1C discharge to 0.01V, constant voltage 0.01C; 0.2C charge to 1.5V; ⑥2C discharge to 0.01V, 2C / 0.2C capacity retention rate is shown in Table 2.

[0153] Capacity retention rate test: 554065 soft pack (≤3Ah, 22 pieces) batteries were tested in a constant temperature test cabinet at 25±2℃. The test conditions are as follows: fully charged at 1C constant current and constant voltage, left for 10 minutes, then discharged at 1C constant current, and charged and discharged 500 times to obtain the capacity retention rate of the battery after 500 cycles.

[0154] Table 1

[0155]

[0156] Table 2

[0157]

[0158] (1) It can be seen from Table 1 and Table 2 that the particle size D10 of the negative electrode materials based on Examples 1-15 of the present invention is between 3.5 µm and 6.0 µm, the particle size D50 is between 7.5 µm and 11.0 µm, and the particle size D90 is between 16.0 µm and 23.5 µm; the oil absorption value of the negative electrode material is between 28 mL / 100 g and 40 mL / 100 g; and the coking factor k of the negative electrode material is between 0.0386 and 0.176. The negative electrode material has a high compaction density, a high first discharge capacity, and a high capacity retention rate after 500 cycles, and has a high energy density, a high rate performance, and a high cycle performance.

[0159] (2) Compared with Example 1, the longer graphitization time in Example 8 and the higher graphitization temperature in Example 11 can obtain a higher degree of graphitization, which is beneficial to improving the battery capacity and the compaction density, but it will reduce the interlayer spacing, which is not conducive to the insertion and deinsertion of lithium ions, resulting in a decrease in high-rate discharge performance and a decrease in cycle capacity retention rate, and slightly reducing the cycle performance and rate performance of the negative electrode material.

[0160] (3) Compared with Example 1, the lower graphitization temperature in Examples 9 and 10 results in a negative electrode material having a lower degree of graphitization, which results in a decrease in the battery capacity and compaction density of the negative electrode material. However, the interlayer spacing is increased, which is beneficial to the embedding and de-embedding of lithium ions, resulting in an improvement in the high-rate discharge performance and an increase in the cycle capacity retention rate, thereby obtaining a negative electrode material with higher cycle performance and rate performance.

[0161] (4) Compared with Examples 1-7, the negative electrode material prepared in Example 12 has a significantly lower Dn10, and the proportion of small particles is large, which is conducive to the embedding and deintercalation of lithium ions, resulting in an increase in high-rate discharge performance, but the contact area with the electrolyte is large, the area of ​​SEI film formation is also large, and the first efficiency will be low. The negative electrode material prepared in Example 13 has a significantly larger Dn10, and the proportion of small particles is small, which is not conducive to the embedding and deintercalation of ions, resulting in a decrease in high-rate discharge performance.

[0162] (5) Compared with Examples 1-7, the volume proportion of small-sized particles between 1 μm and 3 μm in the negative electrode material prepared in Example 14 was significantly reduced to 3.8%, and the lithium ion transmission path was reduced, resulting in reduced high-rate discharge performance and poor rate performance of the negative electrode material. Compared with Example 1, the volume proportion of small-sized particles between 1 μm and 3 μm in the negative electrode material prepared in Example 15 was increased to 7.2%. The large proportion of small particles can increase the contact area with the electrolyte and promote the migration of lithium ions, thereby improving the charge and discharge efficiency and rate performance, but will lead to a decrease in the initial efficiency and compaction density.

[0163] (6) Compared with Examples 1-7, the negative electrode material prepared in Comparative Example 1 has significantly lower D90 (15.0 μm) and coca factor (0.0376), a smaller proportion of large particles, and a larger specific surface area, resulting in a significantly reduced capacity retention rate of the negative electrode material after 500 cycles, and poor cycle performance of the negative electrode material.

[0164] (7) Compared with Examples 1-7, the negative electrode material prepared in Comparative Example 2 has a significantly lower D50 (7.0 μm) and a significantly higher D90 (28.0 μm), resulting in two extreme cases of particle size distribution. The particle size distribution is uneven, resulting in a significant decrease in the capacity retention rate of the ink negative electrode material after 500 cycles, and the negative electrode material has poor cycle performance.

[0165] (8) Compared with Examples 1-7, the negative electrode material prepared in Comparative Example 3 has a significantly higher D10 (6.8 μm), and the proportion of small particles is small, which is not conducive to the insertion and deinsertion of lithium ions, resulting in reduced high-rate discharge performance and reduced capacity retention rate after 500 cycles, and the cycle performance and rate performance of the negative electrode material are poor.

[0166] (9) Compared with Examples 1-7, the negative electrode material prepared in Comparative Example 4 has a significantly higher D50 (11.7 μm) and a larger overall particle size, which is not conducive to the insertion and extraction of lithium ions, resulting in reduced high-rate discharge performance and poor rate performance of the negative electrode material.

[0167] (10) Compared with Examples 1-7, the negative electrode material prepared in Comparative Example 5 has a significantly lower D50 (7.0 μm) and a significantly higher angle of repose (68°), a smaller overall particle size, a larger specific surface area, and poor particle fluidity, resulting in a significantly reduced capacity retention rate after 500 cycles and poor cycle performance of the negative electrode material.

[0168] (11) Compared with Example 2, Comparative Example 6 did not perform the first heat treatment, and the negative electrode material prepared resulted in severe agglomeration of the product and a significant increase in particle size, which was not conducive to the insertion and deinsertion of lithium ions, resulting in a significant decrease in high-rate discharge performance. In addition, the failure to perform the first heat treatment resulted in more volatiles remaining on the surface of the material. The surface of the negative electrode material obtained by subsequent carbonization and graphitization treatments had more edges and corners, which increased the consumption of electrolyte, resulting in a decrease in the capacity retention rate after 500 cycles. The high-rate discharge performance and cyclability of the prepared negative electrode material were poor.

[0169] (12) Compared with Example 2, the negative electrode material prepared in Comparative Example 7 without the second heat treatment resulted in serious agglomeration of the product and a significant increase in particle size, which was not conducive to the insertion and deinsertion of lithium ions, resulting in a significant decrease in high-rate discharge performance. In addition, the temperature was directly increased for pre-carbonization after the first heat treatment, resulting in defects such as microcracks and pores on the surface of the final negative electrode material, which affected the service life of the graphite and resulted in a decrease in the cycle capacity retention rate. The high-rate discharge performance and cyclability of the prepared negative electrode material were poor.

[0170] (13) Compared with Example 2, Comparative Example 8 did not undergo heat treatment, and the negative electrode material prepared therefrom resulted in severe agglomeration of the product, with a significantly increased particle size, which was not conducive to the insertion and extraction of lithium ions, resulting in a significant decrease in high-rate discharge performance. In addition, the negative electrode material obtained by directly heating up the temperature for pre-carbonization treatment without undergoing heat treatment had a large number of edges and corners as well as defects such as microcracks and pores on the surface, which significantly reduced the strength and impact toughness of the graphite material, resulting in a decrease in the capacity retention rate after 500 cycles. The high-rate discharge performance and cyclability of the prepared negative electrode material were poor.

[0171] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A negative electrode material, characterized in that: The negative electrode material comprises graphite, and in the cumulative volume particle size distribution of the negative electrode material, the particle size D10 is 3.5 µm to 6.0 µm, the particle size D50 is 7.5 µm to 11.0 µm, and the particle size D90 is 16.0 µm to 23.5 µm; the oil absorption value dbq of the negative electrode material is 28 mL / 100 g to 40 mL / 100 g; the cocaine factor k of the negative electrode material is greater than or equal to 0.0386 and less than or equal to 0.176, wherein, PD (5T) is the compaction density of the negative electrode material at a pressure of 5T, in g / cm 3 .

2. The negative electrode material according to claim 1, characterized in that The negative electrode material has at least one of the following characteristics: (1) The compaction density of the negative electrode material at a pressure of 5T is 1.70 g / cm 3 Up to 1.85 g / cm 3 ; (2) The particle size Dn10 of the negative electrode material is 0.9 μm to 1.4 μm, the particle size Dn50 is 1.7 μm to 2.6 μm, and the particle size Dn90 is 5.0 μm to 7.0 μm; (3) In the cumulative volume particle size distribution of the negative electrode material, the volume proportion of the negative electrode material with a particle size in the range of 1 μm to 3 μm is 5.5% to 6.5%.

3. The negative electrode material according to claim 1, characterized in that The negative electrode material has at least one of the following characteristics: (1) The graphite has a graphitization degree of 89% to 92.5%; (2) The interlayer spacing between adjacent graphite sheets in the graphite is 3.3600Å to 3.3630Å; (3) The Al content in the negative electrode material is not more than 10 ppm by weight; (4) The water content of the negative electrode material is not more than 0.05% by weight; (5) The repose angle of the negative electrode material is 50° to 65°.

4. The negative electrode material according to claim 1, characterized in that The negative electrode material has at least one of the following characteristics: (1) The specific surface area of ​​the negative electrode material is 1.0 m 2 / g to 1.9 m 2 / g; (2) The graphite includes artificial graphite and / or natural graphite; (3) The graphite includes at least one of petroleum coke-based graphite, asphalt coke-based graphite, and needle coke-based graphite; (4) The tap density of the negative electrode material after 1000 vibrations is 0.95 g / cm 3 Up to 1.3 g / cm 3 .

5. The negative electrode material according to any one of claims 1 to 4, characterized in that The negative electrode material has at least one of the following characteristics: (1) The initial discharge capacity of the negative electrode material is 338 mAh / g to 343 mAh / g; (2) The first discharge efficiency of the negative electrode material is above 93%.

6. A method for preparing a negative electrode material, characterized in that: The following steps are involved: Step S1, crushing the coke raw material to obtain a crushed material; wherein the cumulative volume particle size distribution of the crushed material is that the particle size D10 is 3.5 μm to 6.0 μm, the particle size D50 is 7.5 μm to 11.0 μm, and the particle size D90 is 16.0 μm to 23.5 μm; Step S2, under an inert gas atmosphere, heating the crushed material to a first temperature for a first heat treatment, heating the crushed material after the first heat treatment to a second temperature for a second heat treatment, heating the crushed material after the second heat treatment to a third temperature for a pre-carbonization treatment, wherein the pre-carbonization treatment time is 8 hours to 15 hours; the first heat treatment temperature is 300°C to 500°C, the second heat treatment temperature is greater than or equal to 400°C and less than 800°C, and the pre-carbonization treatment temperature is greater than or equal to 800°C and less than 1500°C; the second heat treatment temperature is greater than the first heat treatment temperature, and the pre-carbonization treatment temperature is greater than the second heat treatment temperature; the ratio of the first heat treatment time, the second heat treatment time and the pre-carbonization treatment time is (1-3): (2-4): (4-6); Step S3, graphitizing the crushed material after the pre-carbonization treatment.

7. The method for preparing the negative electrode material according to claim 6, characterized in that: The method for preparing the negative electrode material has at least one of the following characteristics: (1) In step S1, the coke raw material includes at least one of petroleum coke, pitch coke and needle coke; (2) In the step S1, the coke raw material is crushed by a jaw crusher and then crushed and shaped to obtain the crushed material; (3) The step S2 further includes turning the crushed material over during the heating to the first temperature, the heating to the second temperature, and the heating to the third temperature, and the turning is performed for 10 minutes to 30 minutes every time the temperature rises by 100°C to 300°C; (4) In step S2, the oxygen content in the inert gas atmosphere is no more than 5% by volume; (5) In step S3, the temperature of the graphitization treatment is greater than or equal to 2500° C. and less than or equal to 3000° C.; (6) In the step S3, the heat preservation time of the graphitization treatment is greater than or equal to 8 days and less than or equal to 10 days.

8. The method for preparing the negative electrode material according to claim 6 or 7, characterized in that: The method for preparing the negative electrode material has at least one of the following characteristics: (1) In step S2, the equipment for the pre-carbonization treatment is a carbonization drum kiln; (2) In the step S3, the graphitization furnace type is selected from any one of an inner series furnace, a box furnace, and an Acheson furnace.

9. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer bonded to the negative electrode current collector, characterized in that: The negative electrode active material layer includes the negative electrode material according to any one of claims 1 to 5 or the negative electrode material prepared by the method for preparing the negative electrode material according to any one of claims 6 to 8.

10. A lithium ion battery, characterized in that: It comprises a negative electrode, and the electrode sheet used for the negative electrode is the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Lithium ion battery anode material prepared from cryptocrystalline graphite and preparation method thereof

    CN105047909A

  • Electrode material and secondary battery

    CN109461934A

  • Negative electrode active material and lithium ion battery with improved high-voltage quick charge cycle performance

    CN111533120A

  • Pre-carbonization method of lithium battery negative electrode material

    CN112678813A

  • Artificial graphite primary particle, composite graphite material, preparation method and application

    CN112758921A

Cited By

  • Battery monomer, battery device and energy storage device

    CN121507092A